Does Management Entrenchment Influence Fraudulent Financial Statement ? - Aisya Maulida Rahmawati; Agung Juliarto (Politeknik Ganesha Medan, 2025)
The increase in fraud among public companies has increased public concern as investors, auditors, creditors and other stakeholders. They speculated that management had committed fraud in the financial statement. This research aims to examine the influence of management engagement on fraud in financial reports. Factor analysis of three variables, namely managerial ownership, board independence and audit committee is used to analyze management entrenchment. The population in this study are mining companies registered on the IDX in 2020-2022. Sample selection was carried out using purposive sampling technique and obtained 108 samples. This research uses logistic regression analysis using the e views 12 application. The results of the analysis show that the audit committee has a negative influence while managerial ownership and board independence have no influence. And partially, institutional ownership, board independence and audit committee variables have no influence on financial statement fraud. The research implications are intended for parties who need information regarding the opportunities for fraudulent financial statements to arise in mining companies.